A incidência sociespacial da taxa de ocupação sobre os terrenos e acrescidos de marinha da Amazônia Oriental: o caso da primeira légua patrimonial do município de Belém/PA - ALBUQUERQUE JÚNIOR, Vicente Férrer de (Universidade Federal do Pará, 2023)
The rent, the occupancy rate and the laudemium are property charges, collected by the Federal Government, due to exclusive and long-lasting use of navy lands, those located 33 meters, on the way to the continente, counted by the middle high-water line of 1831. The Amazon estuarian zone has a high occurrence of navy lands, but it needs more studies about property charges collected on such zones. This academic work is interested, then, to study the socio spatial impact of the property charges on the long-lasting navy lands and its increments and its impact on Eastern Amazon, in particular on the first heritage league territory of Belém/PA, as a goal to analize the equity tax isonomy measure and the third part inmate contributive capacity would be applied to incident occupancy rate collection in union sea land property located on the first heritage league territory of Belém/PA. Its specific goals are to do a literature review on union sea land property, use policy, demarcation procedure, its legal status and its aplication related to riverbanks in the first heritage league of Belém/PA; analize the inicial fundraiser collection of the navy lands and its increments, the matrix rule of the incidence, the isonomy cases and the intergovernamental transfers; to check the socio-spatial occurrence of occupancy rate and its relation with third part’s inmate contributive capacity and the exemption hypotheses. This academic work is justified on fiscal justice required application regarding the property charges on union sea land property. It establishes as a deductive scientific method, used in a qualitative research. The procedure method is the study case of the navy lands and its increments on the first heritage league on Belém/PA, made through document and literature research techniques. Based on the research, it’s indicated that, in the socio-spatial context, the main use policy applied to navy lands and its increments located on methodological clipping área it’s the occupancy policy, occupancy rate taxable event, economically more serious than the rent, whose has a concentraded collection on lowland zones without basic sanitation, mostly occupied by low-income population. It appears that, despite the requirement to apply the contributive capacity and the tax isonomy related to property charges, on study zone, the occupancy rate focuses without distinction, even to those who could benefit from the equity tax exemption.